George T. Scanlon 1925–2014 - Abdulfattah, Iman R..
Born in Pennsylvania on April 23, 1925, George T. Scanlon was more than just a scholar of Islamic art and architecture; he was a true Renaissance man who paved the way in areas as wide-ranging as salvage archaeology and scholarly writing. One would have to refer back to his vocation as a young Naval officer to find the wellspring of his intrepid career, since it was his service in the armed forces that played an important role in shaping his academic and professional trajectory. According to one of Scanlon’s oldest friends, he volunteered to join the US Navy at around the age of 18, and was first active in the Second World War from 1942. One of the advantages of his service was eligibility to enroll in the V-12 Navy College Training Program, an initiative created by the American government during the wartime period to augment declining college attendance and grant degrees to prospective officers. It was through this program that he received a Bachelors of Science in Chemistry from Villanova College in 1945. As a war veteran he was also a beneficiary of the G.I. Bill, which enabled him to attend the prestigious Swarthmore College to earn a Bachelor of Arts in Literature and History in 1950. Through ties at Swarthmore he taught English for two years at the Friends Boys School in Ramallah (1950–1951), on a fellowship from the Friends Service Committee; and it was from Ramallah, so I have been told, that Scanlon visited Egypt for the first time.